Towards silent micro-air vehicles: optimization of a low Reynolds number rotor in hover. Issue 8 (November 2019) - Serré, Ronan; Gourdain, Nicolas; Jardin, Thierry; Jacob, Marc C.; Moschetta, Jean-Marc
The demand in micro-air vehicles is increasing as well as their potential missions. Either for discretion in military operations or noise pollution in civilian use, noise reduction of micro-air vehicles is a goal to achieve. Aeroacoustic research has long been focusing on full scale rotorcrafts. At micro-air vehicle scales however, the hierarchization of the numerous sources of noise is not straightforward, as a consequence of the relatively low Reynolds number that ranges typically from 5000 to 100, 000 and low Mach number of approximately 0.1. This knowledge, however, is crucial for aeroacoustic optimization and blade noise reduction in drones. This contribution briefly describes a low-cost, numerical methodology to achieve noise reduction by optimization of micro-air vehicle rotor blade geometry. Acoustic power measurements show a reduction of 8 dB(A). The innovative rotor blade geometry allowing this noise reduction is then analysed in detail, both experimentally and numerically with large eddy simulation using lattice Boltzmann method. Turbulence interaction noise is shown to be a major source of noise in this configuration of low Reynolds number rotor in hover, as a result of small scale turbulence and high frequency unsteady aeroadynamics impinging the blades at the leading edge.